2015
DOI: 10.1039/c4cc08218d
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of robust Zr(iv)-based metal–organic framework films via a postsynthetic ligand exchange

Abstract: A facile and efficient fabrication approach for homogeneous, crack-free UiO-66 films with exceptionally high crystallinity and tunable thickness on a transparent and conductive glass substrate is reported. Two functionalized species, a catechol ligand and a Fe2 complex with structural resemblance to the active site of [FeFe] hydrogenase, were introduced into the MOF films via a postsynthetic exchange. Voltammetric studies show the [FeFe] complex in the thinner UiO-66 films (2-5 μm) can be reduced electrochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
84
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 109 publications
(89 citation statements)
references
References 30 publications
2
84
0
3
Order By: Relevance
“…Similarly, UiO‐66 thin films grown on FTO substrates were postsynthetically exchanged with CAT‐bdc (2,3‐dihydroxy‐1,4‐benzenedicarboxylate), resulting in incorporation of chelating units (63 % CAT‐bdc) that in turn could be postsynthetically metalated with aqueous FeCl 3 solutions in a two‐step process . PXRD and SEM indicated that crystallinity and particle morphology were retained, and with this general procedure established, attempts to incorporate [FeFe](dcbdt)(CO) 6 were investigated.…”
Section: Postsynthetic Exchangementioning
confidence: 99%
“…Similarly, UiO‐66 thin films grown on FTO substrates were postsynthetically exchanged with CAT‐bdc (2,3‐dihydroxy‐1,4‐benzenedicarboxylate), resulting in incorporation of chelating units (63 % CAT‐bdc) that in turn could be postsynthetically metalated with aqueous FeCl 3 solutions in a two‐step process . PXRD and SEM indicated that crystallinity and particle morphology were retained, and with this general procedure established, attempts to incorporate [FeFe](dcbdt)(CO) 6 were investigated.…”
Section: Postsynthetic Exchangementioning
confidence: 99%
“…The immobilized [FeFe] sites had a substantially enhanced performance for photochemical hydrogen production in water at pH = 5, and this was ascribed to the high stability of the active sites on the MOF strut under the photocatalysis conditions. Following this study, the [FeFe] complex was also introduced in a MOF film, and the electrochemical analysis of the film showed that the complex could be electrochemically reduced in solution as the free complex . Feng's group synthesized a MOF that incorporated both the [FeFe] photocatalytic sites and porphyrin photosensitizers .…”
Section: Functionalization Of Mofs For Photocatalytic Solar Fuel Prodmentioning
confidence: 99%
“…[27] UiO-66 membranes and thin films have been prepared by Langmuir-Blodgettd eposition, [29] electrophoretic deposi-tion, [30] electrochemical deposition, [31] and solvothermal synthesis methods. [32][33][34] Herein, an optimized solvothermalp rotocol was appliedt od eposit dense UiO-66t hin films on conducting substrates whose surfaces were pre-functionalized with as elfassembled monolayer (SAM) of 1,4-benzendicarboxylic acid (BDC). [18,19,34,35] Instead of drying with air flow,v acuum, or thermal treatment previously used for solvothermally synthesized UiO-66 films, [32][33][34] we applied the supercritical process, which has been demonstrated as an effective route to activating MOF powder materials without pore collapse, [36][37][38] to dry assynthesized MOF thin films in order to avoid the development of capillarys tress, which has been thought to contribute to the formation of defects.…”
mentioning
confidence: 99%
“…[32][33][34] Herein, an optimized solvothermalp rotocol was appliedt od eposit dense UiO-66t hin films on conducting substrates whose surfaces were pre-functionalized with as elfassembled monolayer (SAM) of 1,4-benzendicarboxylic acid (BDC). [18,19,34,35] Instead of drying with air flow,v acuum, or thermal treatment previously used for solvothermally synthesized UiO-66 films, [32][33][34] we applied the supercritical process, which has been demonstrated as an effective route to activating MOF powder materials without pore collapse, [36][37][38] to dry assynthesized MOF thin films in order to avoid the development of capillarys tress, which has been thought to contribute to the formation of defects. Alternatively,t he thin films were simply dried with an itrogen (N 2 )f low and then treated with PDMS via ap rocess that has been extensively used to fabricate stampsi ns oft lithography: [39] PDMS precursor was cast and cured on the dried MOF thin films, which were subsequently separated from the elastomerl ayers by pealing.F inally,t he molecular sieving capability of UiO-66 thin films on conducting substrates were evaluated by electrochemical measurements for three redox probes.…”
mentioning
confidence: 99%
See 1 more Smart Citation